Legal Politics for Eradicating Criminal Acts of Corruption Related to Roles and Responsibilities of State-Owned Bank Board of Directors - Septiandri, Ivon; Lie, Gunardi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Legal policy determines the form, direction, and substance of the laws to be enacted. The process of lawmaking is always influenced by political movements, and the political role of political institutions is crucial. The rampant corruption in Indonesia makes the formation of laws related to corruption eradication very dynamic. Corruption crimes in Indonesia require more in-depth study in the context of the process of forming legal policies for their eradication, particularly in the realm of state-owned banks, regarding clear boundaries to minimize criminalization while maintaining justice. Article 9G of Law Number 1 of 2025, concerning the Third Amendment to Law Number 19 of 2003 states that members of the Board of Directors of BUMN are not state administrators, this serves to make the role of the board of directors more professional, however, Law Number 16 of 2025 concerning the Fourth Amendment to Law Number 19 of 2003 concerning State-Owned Enterprises actually eliminates Article 9G which existed in the previous law. The article does not directly address the activities of Corruption Crimes, but by eliminating the inclusion of the clause not being a state administrator has the potential for criminalization because the boundary between pure state losses and business losses is very thin, so it is necessary to have clear boundaries regarding the responsibility of the Directors of State-Owned Banks. Losses that occur in State-Owned Banks are not immediately considered state losses, if they meet certain limits called the Business Judgment Rule (BJR). Directors who cannot be held accountable if there is good faith, reasonable prudence (Due Care) based on risk management and Good Corporate Governance (GCG), and there is no Conflict of Interest (No Conflict of Interest).